Legiones, provincias, classes... Morceaux choisis - Reddé, Michel (B@sic, 2022)
This book brings together forty-two articles illustrating different scientific themes addressed during the career of Michel Reddé, director of studies at the École pratique des Hautes Études. The title is borrowed from a well-known passage by Tacitus (Annals, 1.9.5) which describes the state of the Roman world in 14 AD in these terms: "the ocean sea or distant rivers served as barriers to the Empire; legions, provinces, fleets, everything was linked". These texts have been classified into five sections ("The role of the sea", "Rome's Saharan frontiers", "The Roman army, Gaul, Germania", "Around Alesia", "Aspects of Gaul"). They have been put into perspective by thematic introductions and are accompanied by bibliographical additions to take account of the progress of research subsequent to their initial publication. The subjects treated are apparently heterogeneous: fleets, legions, borders, provinces as far apart as Gaul and Egypt, works devoted to the limes but also to agriculture... What is the connection? The answer is in Tacitus himself: everything was linked, indeed, the security provided on the borders by the legions, the loyalty and prosperity of the provinces, the civil peace and opulence of an empire centred around an inland sea on which the military fleets ensured the continuity of power and communications from one shore to the other. Most of these articles are accompanied, where possible, by references to videos, audio lectures and audio books intended for a wide audience.